Diversifikasi Pendapatan Berbasis Bioteknologi Memanfaatkan Energy Baru Terbarukan pada Kelompok Koi Lovers di Desa Bongopini - Humena, Steven; Syamsir, Syamsir; Ariawan, Ariawan (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: Bongopini Village is a village in Tilongkabila District, Bone Bolango Regency, Gorontalo Province. It has four hamlets with a population of 1,425. There are 5 groups of freshwater fisheries cultivation with a total of 24 land pond plots with an area of approximately 10 ha. Koi Lovers Farm is one of the fish cultivator groups that specializes in cultivating koi fish Methodology: The Community Partnership Program at the Koi Lovers Farm in Bongopini village, Tilongkabila District, Bone Bolango Regency, is a community service program that aims to help koi fish breeders and the community in diversifying their biotechnology-based income by utilizing new and renewable energy to improve community welfare. Programs that have been implemented include providing knowledge and skills in business management, Koi fish cultivation management training, Training and practice in making a Recirculating Aquaculture System (RAS) using solar energy, Income diversification training in the form of an aquaponic system and providing assistance for koi fish broodstock for hatching, Results: several stages of evaluation were carried out after the activity was carried out, such as evaluation from activity partners, 83.34% of the partner group understands the purpose of income diversification. There has been an increase in partner products by 100% who previously only tried koi fish, increased by hydroponic vegetables, and as many as 83.33% of partners strongly agree that cultivating lettuce plants can provide additional income for them, as well as additional partner income of IDR 600,000. Limitation: hydroponic farming activities require extra care, apart from coinciding with the rainy season, it also requires more time to control the water in the hydroponic installation. Contribution: The Koi Lovers group actively participates in the activities carried out, with the knowledge that has been given they have been able to operate hydroponic installations independently to increase their income.